ISOLATION AND IDENTIFICATION OF Staphylococcus aureus FROM TICKS ON THE CATTLE IN BASRA CITY (Basrah Journal of Veterinary Research)
Ticks are an important external parasite have a mechanical affect through an imbibing blood of the host and transferring a pathogenic bacteria or a virus. The present  study was focusing on the isolation of bacteria from the ticks parasitized cattle in north of Basra city,This study was conducted in north of Basrah (Qurna district) from February to July 2017Atotal number of 80cattle parasitized with ticks were samplesIsolated ticks were identified as Hyalomma to recognize what types of bacteria might be existed in these ticks, some of the cultures and biochemical tests were used. As a consequence, Staphylococcus aureus being identified in 14 of cattle sampled that infected with ticks. Regarded to present study, Staphylococcus aureusis one of the most pathogenic bacteria that can have an  impact on an animal health production and  this study that conducted from little studies in Iraq especially in Basrah about diagnosis of bacterial infection from Ticks.